Analytical Solution and Simulation of Oil Deliverability Analysis for Reorientation Hydraulic Fracture in Low-Permeability Reservoirs. (21st July 2021) - Qiu, Xinyu; Kang, Botao; Liu, Pengcheng; Hao, Shengye; Zhou, Yanglei; Shan, Ce; He, Houfeng; Xu, Liang
Abstract : The hydraulic refracturing operations are often used to improve oil deliverability in the low-permeability reservoir. When the development of oilfields has entered a high water cut stage, oil deliverability can be promoted by refracturing reservoirs. The orientation of the new fracture formed by refracturing will be changed. The new formed fracture is called reorientation fracture. To calculate the oil deliverability of the refracture wells, a three-section fracture which includes reorientation fracture was established. The multiwell pressure drop superposition theory is used to derive the analytical solution of the refracture wells which includes the reorientation fracture. The numerical simulation was conducted to validate the results of the analytical solution. Comparing the refracture well deliverability of reorientation and nonreorientation, permeability, deflection angle, and the length of reorientation fracture will jointly control the productivity of refracture well. When the permeability in the direction of maximum principal stress is greater than the permeability in the direction of minimum principal stress, the capacity of reorientation fractures is relatively large. The deflection angles and the length of the reorientation fracture will directly affect the drainage area of the fracture, thus affecting productivity. The reorientation fractures generated by repeated fracturing have great potential for improving oil deliverability in the anisotropic low-permeability reservoirs.